Comparative investigation on the influence of spent foundry sand as partial replacement of fine aggregates on the properties of two grades of concrete. (15th May 2015) - Siddique, Rafat; Singh, Gurpreet; Belarbi, Rafik; Ait-Mokhtar, Karim; Kunal,
Highlights: Use of spent foundry sand (SFS) as partial replacement of sand. Sand has been replaced with 0%, 5%, 10%, 15%, and 20% SFS. Comparative study of the influence of SFS on properties of two grades of concrete. Inclusion of SFS in concrete resulted in denser and durable concrete. Abstract: An experimental program was carried out to study the influence of spent foundry sand (SFS) as partial replacement for fine aggregates (natural sand) on two grades of concrete mixtures. Two control concrete mixtures (M20 & M30) were designed to have 28-day compressive strength of 30 MPa and 40 MPa. Then, fine aggregate (natural sand) was replaced with five percentages (0%, 5%, 10%, 15%, 20%) of SFS by weight. Comparative performance of both types of concrete (M20 & M30) was investigated by measuring compressive strength, splitting tensile strength, modulus of elasticity, chloride permeability, and ultra sonic pulse velocity up to the age of 365 days. Test result indicate a marginal increase in strength and durability properties of plain concrete by inclusion of SFS as a partial replacement of fine aggregate. Further, influence of incorporating spent foundry sand is more prominent on M20 grade of concrete as it enhances the strength and durability properties better than M30 grade of concrete.